Modernize your IBM DB2 for IBM z/OS maintenance with utility autonomics - Brown, Dean (IBM redbooks., 2015)
This book guides you through the business reasons for adopting autonomic solutions, and provides step-by-step guidance to implement these capabilities in your DB2 for z/OS configuration. IBM DB2 for IBM z/OS helps lower the cost of managing data by automating administration, increasing storage efficiency, improving performance, and simplifying the deployment of virtual appliances. By automating tasks such as memory allocation, storage management, and business policy maintenance, DB2 is able to perform many management tasks itself, freeing up Database Administrators to focus on new projects. With the inclusion of the IBM Management Console for IMSTM and DB2 for z/OS and the Autonomics Director, it is now easier than ever to make a transition by leveraging the strength of the DB2 Utilities Solution Pack for z/OS all in one standardized and centralized interface. --